Knowledge regarding mosquito borne diseases & control measures practiced among a rural population in a southern district of Tamil Nadu, South India - Sudhir Ben Nelson; Vishnu G Ashok; Madiha Nazer; S Manibalan; Madhumitha R.A (Public Health Review: International Journal of Public Health Research, 2017)
Introduction: Vector-borne diseases account for over 17% of all infectious diseases. Up to 700 million people are infected and more than a million die each year from mosquito-borne illness. The extent of people’s cooperation can determine the success or failure of the entire campaign for Mosquito control.Methods: A cross-sectional observational study was carried out in Kanyakumari district among 180 individuals selected through multi-stage sampling. Data was collected using a semi structured interview schedule.Results: Every one of the study participants knew that mosquitoes spread diseases. Dengue was the most common disease related to Mosquito. Among the respondents, 113(62.7%) answered that coconut shells most common mosquito breeding place. Coconut shells (66%) & Open drainages (61.1%) were reason for water stagnation inside & outside their own compound respectively. 71.1% have seen mosquito larva in stagnant water around their house and among them 75.8% have done something to kill larva. Most common method used was putting bleaching powder in the larva breeding places (39%) followed by source reduction (26.5%). Bleaching powder was also the most common method (57%) used for prevention of mosquito breeding. 78.9% of the households were using personal protective measures, mosquito coil (59.8%), the most commonly used method. Only 38.5% of them said that fogging was done in their area in past 6 months.Conclusion: A good proportion of the households are taking preventive measures, but still so many households lacks practice or found to be doing wrong practices. Therefore, we recommend that community should be empowered with the right & adequate knowledge.